Por uma comunidade desejante: um estudo sobre Néstor Perlongher e Severo Sarduy - Andrade Júnior, Antonio Francisco de (2011)
This thesis aims at understanding the relationship between the aesthetic and the political in Hispanic American Neo-Baroque literature. Throughout the work, I show how the stereotypes of political and artistic protagonism may involve the regulation and control of homoerotic desire, both in social and cultural production, especially in Argentina and Cuba. Therefore, from the community's problems, I try to reflect on the constant mobility of thought, subjectivity, identity models, and literary forms in contemporary, having as object Néstor Perlongher and Severo Sarduy s oeuvres, produced between the 1960s and 1990s. After the development of my argumentative point of view and explanation of the historical context in which these discourses fall, I am dedicated to the analysis of the performances and the different methods of writing undertaken by Perlongher and Sarduy. In the last part, I highlight the possibility of dialogue between the theoretical and critical issues raised by the reading of both writers.